As influências das práticas de gestão de pessoas na cultura organizacional - Alves, Rodolfo Carlos Souza (2003)
This study had for objective to verify as the practical ones of management of people are influencing the culture of brazilian organizations. To make possible the identification and the analysis, the used ways had been the research of fíeld and the bibliographical one. Also the experience of more than twenty five years of the researcher of this dissertation as professional of the área of human resorces was considered, as consulting and teacher of